Feasibility and effectiveness of cognitive remediation in the treatment of borderline personality disorder. Issue 3 (3rd April 2018) - Vita, Antonio; Deste, Giacomo; Barlati, Stefano; Poli, Roberto; Cacciani, Paolo; De Peri, Luca; Sacchetti, Emilio
ABSTRACT: Several studies have demonstrated that borderline personality disorder (BPD) is associated with neuropsychological deficits and there is evidence that the neurocognitive profile of patients with BPD may be related to the outcome of this disorder. The aim of this study was to investigate the feasibility and the effectiveness of a cognitive remediation intervention in patients with BPD. Thirty patients with a DSM-IV-TR diagnosis of BPD were assessed on clinical, neuropsychological and functional outcome measures at baseline and after 16 weeks of a computer-assisted cognitive remediation (CACR) intervention or treatment as usual (TAU). Patients who received CACR showed a greater improvement in working memory and psychosocial functioning measures than patients treated with TAU. Symptom severity was not significantly affected by CACR treatment. The findings of this pilot study suggest the feasibility and potential effectiveness on specific cognitive domains, but modest clinical usefulness of a computerised modality of cognitive remediation in the treatment of BPD.